1998
DOI: 10.1046/j.1365-8711.1998.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Fast variability of the outflow in the Z CMa system

Abstract: High‐resolution, time‐resolved spectroscopic observations of Z CMa carried out on 1997 January 14–17 are presented. Large night‐to‐night and hour‐to‐hour variations in Hα, Hβ and Na i D P Cygni absorptions, as well as an Hβ emission peak, were observed. Variations in the red wings of the hydrogen emission lines were also detected. The high‐velocity wide‐emission component on the blue side of Hα appeared on January 17. The observations are discussed in the framework of current wind models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The EW of the Hα emission has increased slightly with respect to that of 1991. However, Chochol et al (1998) have found that the daily variations of the Hα emission can be considerable so that small changes over long periods do not permit us to draw any conclusions. We also note here that the Paschen emission lines are not detected in the 1996 spectrum, so that the Ca ii (2) lines do not have to be corrected for the contribution by the Paschen lines. The ESO profiles of the Ca ii (2) lines at 8498 and 8542 Å are very similar to those of the WHT spectrum of December 26.…”
Section: Analysis Of the Spectramentioning
confidence: 94%
See 3 more Smart Citations
“…The EW of the Hα emission has increased slightly with respect to that of 1991. However, Chochol et al (1998) have found that the daily variations of the Hα emission can be considerable so that small changes over long periods do not permit us to draw any conclusions. We also note here that the Paschen emission lines are not detected in the 1996 spectrum, so that the Ca ii (2) lines do not have to be corrected for the contribution by the Paschen lines. The ESO profiles of the Ca ii (2) lines at 8498 and 8542 Å are very similar to those of the WHT spectrum of December 26.…”
Section: Analysis Of the Spectramentioning
confidence: 94%
“…The EW of the Hα emission has increased slightly with respect to that of 1991. However, Chochol et al (1998) have found that the daily variations of the Hα emission can be considerable so that small changes over long periods do not permit us to draw any conclusions.…”
Section: The Emission Linesmentioning
confidence: 94%
See 2 more Smart Citations
“…3, right panel) containing many incoherent variations down to time scales of about 0.3 day. At least a part of these oscillations may have their origin in the night-to-night and hour-to-hour variations of Hα, H β , Na I D P Cygni absorptions and in the H β emission peak (Chochol et al 1998). Also, from speckle observations obtained in the infrared H&K filters Hass et al (1993) reported that both components of the close visual double were varying independently by ∼ 0.5 mag.…”
Section: Z Cmamentioning
confidence: 99%